Tradisi Rokat Tase’ Dalam Perspektif Hukum Islam (Studi Kasus Di Desa Branta Pesisir Kabupaten Pamekasan Madura) - El Amin, Faris (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
Rokat tase' is essentially carried out with the aim of getting safety from all calamities, given smooth fortune, is a form of gratitude and is believed to be able to produce abundant fish catches. In practice, in coastal Branta Village, in the rokat tase ritual, special offerings are usually made which are placed on small boats and then served on top of various fruits and various foods. Shortly before being thrown into the ocean, the contents of the offerings became objects of contention for residents to eat and use.